Cada um se virou como pôde. uma etnografia multissituada a partir de narrativas de docentes sobre digitalização das relações educacionais e o impacto da pandemia de Covid-19 no interior de Goiás - Queiroz, Léia Rodrigues da Silva (2025)
This research analyzes my own narratives and the experiences of my colleagues regarding the use of Information Technology (ICTs) in our daily school routines. The analysis is based on our work environment, a municipal public school offering Early Childhood Education and Elementary School I, located on the outskirts of a municipality in northern Goiás. It reflects on the use of ICTs in the school environment before, during, and after the COVID-19 pandemic, and the social markers of differences, such as race, class, ethnicity, sexuality, gender, and generation. This is an ethnographic, multi-sited study whose overall objective is to analyze teachers' narratives about how they use ICTs in the classroom. During the investigation, the distance of some interlocutors regarding the use of ICTs became evident. It includes accounts of my experiences as a participating researcher and professor at a higher education institution during the pandemic. My research uses an ethnographic, autoethnographic and multi-sited methodology, consisting of field notebooks, participant observation and semi-structured interviews. The results and discussions point to teachers' unpreparedness in using technologies as mediating tools for teaching and learning. In addition to dealing with the school's lack of infrastructure, they also face government neglect, which failed to provide professional, structural, or financial support. Teachers had to overcome these challenges, confronting social and digital inequalities. The difficulties teachers—especially the women who participated in this study—faced in balancing professional demands with their home routines during remote classes were highlighted. This highlights the need for government investment in education, teacher training, and social programs that combat social and digital inequalities.